Between memory and oblivion: the complex experiences of ZAKA volunteers during the Israel-Hamas war (“Swords of Iron”) - Cohen Zada, Oren Cohen (Frontiers in Psychology, 2026)
IntroductionThis qualitative study characterizes the moral-psychological and existential dynamics of 24 ZAKA volunteers during the “Iron Swords” war. It focuses on how the encounter between extreme trauma and a supreme moral-Halakhic mandate (“Chesed Shel Emet”) shapes trauma processing.MethodsThrough in-depth semi-structured interviews, the research examined the volunteers’ experiences of the October 7, 2023, events, their emotional difficulties, and the tension between memory and forgetting.ResultsFour core themes were identified: sensory and emotional overload leading to internal conflict, the role of social support as a pillar for resilience, the “tightrope walk” between memory as a mission and oblivion as a coping mechanism, and the significance of commemoration as a source for Post-Traumatic Growth (PTG).DiscussionThe findings indicate that the Halakhic commitment functions as a unique cultural-religious mediating variable. While it intensifies the risk of Moral Injury due to helplessness, it simultaneously serves as a stable collective meaning anchor that drives a resilient Collective PTG Identity. This study offers critical clinical and ethical insights for emergency organizations.